Negative electrode material, negative electrode plate and secondary battery
By filling the first non -fixed carbon in the pores of natural graphite and covering the second non -fixed carbon on the surface, the micro structure of the negative electrode material is optimized, solving the problem of being difficult to take into account the expansion rate and the first Kuron efficiency, and achieved it. High electrochemical properties and longer battery life.
Patent Information
- Application Number
- CN202411850893.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-16
AI Technical Summary
In the prior art, it is difficult to take into account the expansion rate and the first-time Coulomb efficiency.
By filling the first non -fixed carbon in the pores of natural graphite, and covering the second non -fixed carbon on the surface, the micro structure of the material is optimized and the electrochemical performance of the material is improved. Specific measures include the average value of the ID/IG of the inner region is KA, and the average value of the ID/IG in the inner area to the outer area is K, which meets: 0.4≤ka ≤ 0.7, 0.5 ≤K <0.9.
By optimizing the micro -structure, the embedded and dehydration efficiency of lithium ions was improved, the volume expansion in the charging and discharge process was effectively alleviated, the service life of the secondary battery was prolonged, and the first Kuron efficiency was improved.
Smart Images

Figure CN119340375A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a negative electrode material, a negative electrode sheet and a secondary battery. Background Art
[0002] Lithium-ion batteries are widely used in 3C, power devices, energy storage equipment and other fields due to their advantages such as low self-discharge rate, high charge and discharge efficiency, no memory effect, and long cycle life. Among them, the negative electrode material is an important component of lithium-ion batteries, and its performance directly affects the electrochemical performance of lithium-ion batteries. Natural negative electrode materials have attracted widespread attention due to their advantages such as high specific capacity, low charge and discharge platform, and low cost. However, natural graphite has high anisotropy and internal defects. During the lithium ion embedding process, the volume expansion of graphite is mainly manifested as expansion in the thickness direction. The solvent molecules in the electrolyte will enter the graphite interlayer together with the lithium ions. This process will further increase the expansion of the graphite. At the same time, the embedding of solvent molecules not only increases the volume of graphite, but may also lead to the formation of the SEI film, which is not dense, affecting the first coulomb efficiency of the battery. Summary of the invention
[0003] The main purpose of the present invention is to provide a negative electrode material, a negative electrode sheet and a secondary battery to solve the problem in the prior art that it is difficult to balance the expansion rate and the first coulomb efficiency of the negative electrode material.
[0004] In order to achieve the above object, according to one aspect of the present invention, a negative electrode material is provided, the negative electrode material comprises a core and a coating layer, the coating layer is located on the surface of the core, the core comprises natural graphite and a first amorphous carbon filled in the pores of the natural graphite, and the coating layer comprises a second amorphous carbon; the Raman spectrum of the negative electrode material has a D peak and a G peak, and the intensity ratio of the D peak to the G peak is 1 D / I G The inner core includes an inner region and an outer region outside the inner region, and the outer region is adjacent to the cladding layer; the inner region I D / I G The mean value is K a , the inner and outer regions I D / I G The mean of the ratio is K; satisfying: 0.4≤K a ≤0.7, 0.5≤K<0.9.
[0005] Furthermore, the pore area percentage of the inner core is , meet: 2% ≤ ≤5%.
[0006] Furthermore, the average value of the ratio of the pore area percentage of the inner layer region to the outer layer region is A, which satisfies: 1.2≤A≤2.0.
[0007] Furthermore, the D50 particle size of the negative electrode material is 5-20 μm.
[0008] Furthermore, the shape of the negative electrode material includes at least one of a sphere, an ellipsoid, and a quasi-spherical shape.
[0009] Furthermore, the specific surface area of the negative electrode material is 2~5m 2 / g.
[0010] Furthermore, the tap density of the negative electrode material is 0.9~1.4g / cm 3 .
[0011] Furthermore, the average pore size of the negative electrode material is 10-20 nm.
[0012] A second aspect of the present invention provides a negative electrode sheet, which includes the negative electrode material provided by the first aspect.
[0013] A third aspect of the present invention provides a secondary battery, wherein the secondary battery comprises the negative electrode sheet provided by the second aspect.
[0014] By applying the technical solution of the present invention, the pores of natural graphite are filled with the first amorphous carbon and the surface is coated with the second amorphous carbon, so as to optimize the microstructure of the material and improve the electrochemical performance of the material. D / I G The mean value is K a , the inner and outer regions I D / I G The mean of the ratio is K; satisfying: 0.4≤K a ≤0.7, 0.5≤K<0.9, indicating that the first amorphous carbon can achieve compact filling and reasonable distribution of D peak and G peak, which is helpful to improve the efficiency of lithium ion insertion and extraction, and effectively alleviate the volume expansion during the charge and discharge process, thereby extending the service life of the secondary battery. The negative electrode material is used in the secondary battery, and the first coulomb efficiency can be ≥94%, and the expansion rate of the pole piece after 20 cycles is ≤25.7%. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 A schematic diagram of the Raman Mapping region of a cross-section of a negative electrode material particle in one embodiment of the present invention;
[0016] Figure 2 This is a SEM image of the cross-sectional morphology of the negative electrode material particles in another embodiment of the present invention.
[0017] Figure 3 A schematic diagram of the structure of a secondary battery provided in one embodiment of the present invention during charging;
[0018] Figure 4 A schematic diagram of the structure of a secondary battery during discharge provided by one embodiment of the present invention.
[0019] Description of reference numerals:
[0020] 100 - electrode assembly; 101 - positive electrode sheet; 102 - negative electrode sheet; 103 - isolation membrane. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0022] As described in the background of the present invention, the negative electrode material in the prior art has the problems of high expansion rate and low first coulomb efficiency. In order to solve the above problems, in a typical embodiment of the present invention, a negative electrode material is provided, the negative electrode material includes a core and a coating layer, the coating layer is located on the surface of the core, the core includes natural graphite and a first amorphous carbon filled in the pores of the natural graphite, and the coating layer includes a second amorphous carbon; the Raman spectrum of the negative electrode material has a D peak and a G peak, and the intensity ratio of the D peak to the G peak is 1 D / I G The inner core includes an inner region and an outer region outside the inner region, and the outer region is adjacent to the cladding layer; the inner region I D / I G The mean value is K a , the inner and outer regions I D / I G The mean of the ratio is K; satisfying: 0.4≤K a ≤0.7, 0.5≤K<0.9.
[0023] The negative electrode material of the present invention has a multi-layer composite structure, including a core and a coating layer, wherein the core includes natural graphite and a first amorphous carbon filled in the pores of the natural graphite, and the structure of the negative electrode material is significantly optimized by filling the first amorphous carbon in the core and coating the second amorphous carbon on the surface. The coating layer includes the second amorphous carbon, which covers the surface of the core to form a protective film.
[0024] Specifically, on the one hand, the first amorphous carbon is a highly disordered carbon structure, which can fill the internal pores of natural graphite, effectively reduce the porosity, and increase the density of the particles; in addition, the filling of the first amorphous carbon can also reduce the anisotropy of the negative electrode material, making the diffusion of lithium ions in different directions more uniform, thereby improving the Li + The diffusion rate between graphite layers reduces the Li+ The structural strain generated during the embedding and de-embedding process reduces the expansion rate of the material and improves the structural stability of the material. On the other hand, the coating of the second amorphous carbon helps to reduce the direct contact between natural graphite and the electrolyte, prevents solvent co-embedding, and is conducive to the formation of a stable and dense SEI film during the first charge and discharge process, thereby improving the electrochemical stability of the material and the first coulombic efficiency.
[0025] The Raman spectrum of the negative electrode material has D peak and G peak. The diffraction peak and the corresponding peak intensity can be obtained by Raman spectrum analysis. The D peak is located at about 1350cm -1 , while the G peak is located at about 1580cm -1 The intensity of the D peak is related to the lattice defects, amorphous carbon or disordered structure in the negative electrode material, and the intensity of the G peak is related to the degree of graphitization or order of the graphite material. The intensity ratio of the D peak to the G peak (I D / I G ) is an important parameter to measure the distribution of amorphous carbon and the degree of graphitization inside the material, which reflects the orderliness of the internal structure of the particles of the negative electrode material and the changes in the surface properties. D / I G The higher the value, the more amorphous carbon or defective structure exists in the material. Conversely, the lower the value, the higher the degree of graphitization of the material and the more ordered the structure.
[0026] The negative electrode material has multiple particles, and the I D / I G It can be the inner region I in multiple particles D / I G The arithmetic mean of the inner and outer regions I D / I G The average value of the ratio of the inner region to the outer region in multiple particles can be D / I G The arithmetic mean of the ratio of D / I G The mean value is K a , the inner and outer regions I D / I G The mean of the ratio is K, K a and K are used to characterize the overall structural properties of the negative electrode material.
[0027] K a The value reflects the average distribution of amorphous carbon in the inner layer and the structural defect state of the region. a≤0.7, which can ensure that the inner layer of the graphite particles contains an appropriate amount of amorphous carbon. These amorphous carbons fill the pores between the graphite layers, which can reduce the volume expansion of graphite during the charge and discharge process, improve the structural stability of the material, and delay the shedding of graphite sheets, thereby improving the cycle life of the secondary battery; the appropriate range of K a The value helps to form a more optimized SEI film on the surface and inside of the negative electrode material. The stability of the SEI film directly affects the first coulombic efficiency, while the amorphous carbon in the inner layer can promote the formation of the SEI film and reduce the decomposition of the electrolyte, thereby improving the first coulombic efficiency.
[0028] By limiting 0.5≤K<0.9, it is shown that the structures of the inner and outer regions of the particles are different, the amorphous carbon content of the inner region is relatively high, and the amorphous carbon content of the outer region is relatively low. This shows that the pores in the inner region are filled with the first amorphous carbon, while the outer region maintains a certain degree of order. By optimizing the distribution of amorphous carbon in the inner and outer layers, the relative balance of the lithium ion diffusion rate in the inner and outer regions can be ensured to avoid performance problems caused by too fast or too slow diffusion rate in the inner region; secondly, the loss of lithium ions during charging and discharging is reduced, and the first coulomb efficiency is improved. In addition, it helps to control the stress distribution inside the material, reduce structural damage during charging and discharging, and reduce the risk of graphite flakes falling off, thereby improving the structural stability and cycle life of the material.
[0029] According to the research of the present invention, the application of the above negative electrode material in the secondary battery is helpful to improve the initial coulombic efficiency and reduce the expansion rate. This is because the microstructure of the material is optimized by filling the pores of natural graphite with the first amorphous carbon and coating the surface with the second amorphous carbon; by limiting the inner and outer layer regions of the inner core, the first amorphous carbon is formed in the inner core, and the second amorphous carbon is formed in the outer core, and the second ... D / I G The mean of the ratio and the I D / I G The mean of this special structure combined with I D / I G The limitation can ensure the stability of the overall structure of the material, the small volume change during the lithium ion embedding and de-embedding process, reduce the shedding and expansion of graphite sheets, and reduce the expansion rate of the pole piece during the charging and discharging process. At the same time, it can also ensure that the amorphous carbon on the surface and inside of the negative electrode material is evenly distributed, forming a stable SEI film. The stable and evenly distributed SEI film reduces the direct contact between the electrolyte and the graphite, thereby reducing the ineffective consumption of lithium ions during the first charging and discharging process and improving the first coulomb efficiency. When the negative electrode material is used in a secondary battery, the first coulomb efficiency can be ≥93.5%, and the first coulomb efficiency can be further achieved. ≥94%, the pole piece expansion rate after 20 cycles is ≤27.3%, and the pole piece expansion rate after 20 cycles can be further achieved. ≤25.9%.
[0030] The present invention does not limit K a The test method of K can be any conventional method in the art, as long as the negative electrode material meets the above structural and parameter requirements. For example, in some embodiments, K a , K is obtained by the following steps:
[0031] S11, select n particles of the negative electrode material, and select the i-th rectangular area on the inner core section of the i-th particle; wherein the center of the i-th rectangular area is the center of the inner core section, 1≤i≤n, n≥15, and i and n are both positive integers;
[0032] S12, dividing the i-th rectangular area into an inner rectangular area and an outer rectangular area along the length direction; wherein the inner rectangular area includes the center of the inner core section, and the outer rectangular area is located outside the inner rectangular area;
[0033] S13, obtaining the I of the inner rectangular area and the outer rectangular area in the i-th particle D / I G , respectively denoted as K ai and K bi ;
[0034] S14, calculate K of n particles ai The average value is used to obtain the I of the inner region. D / I G The mean value of K a ;
[0035] S15, by K i =K ai / K bi Calculate the K of the i-th particle i value;
[0036] S16, calculate K of n particles i The average value is used to obtain the I of the inner and outer regions. D / I G The mean of the ratios is K.
[0037] Specifically, in S11, n particles are randomly selected from the negative electrode material, where n is a sufficiently large sample size, and n is usually required to be a positive integer ≥ 15 to ensure the statistical significance and representativeness of the analysis results. Then, the i-th particle can be cut using a slice or an ion beam to expose the inner core section of the i-th particle, and an i-th rectangular area is selected on the inner core section, and the center of the i-th rectangular area is set as the geometric center of the inner core section, that is, the area covers the center position of the particle. Such a selection ensures the representativeness of the analysis area and can reflect the characteristics of the particle inner core. The value range of i is a positive integer from 1 to m.
[0038] In S12, the selected i-th rectangular region is further divided into three parts along the length direction: an inner rectangular region and two outer rectangular regions. The two outer rectangular regions are located on both sides of the inner rectangular region, that is, the outer rectangular region is adjacent to the edge of the inner rectangular region, respectively corresponding to the structural characteristics of the inner region and the outer region in the particle, and the distribution of amorphous carbon can be analyzed by comparing these two regions.
[0039] In S13, Raman spectroscopy is used to scan the inner rectangular area and the outer rectangular area of the i-th particle respectively to obtain Raman spectral data of the two areas; the intensity of the D peak and the G peak can be extracted from the Raman spectrum, and then I D / I G Values, denoted as K ai (I of the inner region of the i-th particle D / I G value) and K bi( I of the outer region of the i-th particle D / I G value).
[0040] In S14, the inner rectangular area I of n particles D / I G The average value is calculated to get K a value, which represents the average I D / I G Value. K a The value reflects the relative content of amorphous carbon in the inner layer and the average state of the degree of structural disorder.
[0041] In S15, for each particle, K i =K ai / K bi Calculate and obtain the inner rectangular area and the outer rectangular area I in the i-th particle D / I G The ratio of the values, i.e., the K of the i-th particle i This ratio can reflect the difference in structural characteristics between the inner and outer regions of the i-th particle.
[0042] In S16, K for n particles i The values are averaged to get the K value, which is the I value of the inner rectangular area and the outer rectangular area. D / I G K reflects the ratio of the inner layer area to the outer layer area I in the entire negative electrode material. D / I G The mean of the ratio of is used to indicate the difference in property characteristics between the inner and outer regions of the particle.
[0043] The i-th rectangular area is set to more accurately analyze the distribution of amorphous carbon at different depths of negative electrode material particles. In some embodiments, the width of the i-th rectangular area is 1-6 μm, ensuring that the width of the i-th rectangular area is small enough to finely detect changes in the internal structure of the material. In some embodiments, the two endpoints in the length direction or the two endpoints on the diagonal line of the i-th rectangular area are located on the edge of the core section, so that the i-th rectangular area can span the entire core section, which can ensure that the obtained data is both accurate and representative, and is helpful for analyzing the distribution of amorphous carbon at different depths.
[0044] The inner rectangular area represents the average state of the inner region of the particle, and the outer rectangular area represents the average state of the outer region of the particle. In some embodiments, the center of the inner rectangular area is the center of the inner core section, ensuring that the inner rectangular area is the inner region of the particle, and the filling uniformity of amorphous carbon inside the particle can be more accurately evaluated. In some embodiments, the length of the inner rectangular area is equal to 1 / 2 of the length of the i-th rectangular area. This ensures that the depth of the inner rectangular area is sufficient to touch the internal structure of the particle, rather than just the surface or near-surface area.
[0045] In some embodiments, the core has a pore area percentage of , meet: 2%≤ ≤5%. By controlling the core pore area ratio between 2% and 5%, the volume change of the negative electrode material during the charge and discharge process can be reduced, and the particles can be prevented from rupturing due to excessive expansion, thereby improving the structural stability of the material. In addition to further improving the initial coulomb efficiency and reducing the expansion rate, it also helps to build a continuous conductive network, reduce the resistance to electron and lithium ion transmission, and improve the efficiency and safety of secondary batteries.
[0046] The average value of the ratio of the pore area percentage of the inner layer region to the outer layer region is A, which satisfies: 1.2≤A≤2.0. By limiting the average value of the ratio of the pore area percentage of the inner layer region to the outer layer region, it is helpful to build a more uniform pore distribution inside the negative electrode material, which is conducive to the uniform embedding and de-embedding of lithium ions, reducing local stress, and further improving structural stability and first coulomb efficiency; in addition, the appropriate pore area and uniform pore distribution can promote more efficient diffusion of lithium ions between graphite layers, shorten the charge and discharge time, and improve the power density of the secondary battery.
[0047] In the present invention, the exposed surface obtained by cutting the negative electrode material particles can be called a section, and the structural characteristics of the material inside can be displayed through the section. The section can be cut through the center of the particle and perpendicular to the length direction or width direction of the particle. The section can be used for microstructural analysis, such as scanning electron microscopy (SEM), Raman spectrometer, etc.
[0048] The present invention does not limit , A test method, can be conventional methods in the art, as long as the negative electrode material meets the above structural and parameter requirements. In some embodiments, , A is obtained by the following steps:
[0049] S21, select m particles of the negative electrode material, and divide the inner core section of the jth particle into a central region and an edge region; wherein the edge region is located at the periphery of the central region, 1≤j≤n, m≥20, and j and m are both positive integers;
[0050] S22, obtain the pore area ratio of the jth particle, the pore area ratio of the central area and the pore area ratio of the edge area, respectively , and ;
[0051] S23, calculate the m particles i The average value is used to obtain the pore area percentage of the core ;
[0052] S24, via A j = aj / bj Calculate the A of the jth particle j value;
[0053] S25, calculate A of m particles j The average value is the average value of the ratio of the pore area percentage of the inner layer area to the outer layer area, that is, A.
[0054] Specifically, in S21, m particles are randomly selected from the negative electrode material, where m is a sample size large enough to ensure the representativeness of the statistical sample, and m is usually a positive integer ≥ 20. The jth particle can be cut using a slice or an ion beam so that the inner core section of the jth particle is exposed and divided into two parts: a central area and an edge area. The edge area is located on the periphery of the central area, and this division helps us analyze the distribution of pores in different areas, thereby evaluating the consistency of the internal structure of the material. The value of j ranges from 1 to m.
[0055] In S22, the SEM (scanning electron microscope) image can be used to identify and measure the pore area on the cross section of the particle core through software tools. The pore area is divided by the total cross section area of the entire particle core to obtain the pore area ratio of the jth particle, that is, j, which reflects the pore distribution of the entire particle. Similarly, by identifying and measuring the pore area of the central region, and dividing the pore area of the central region by the total area of the central region, the pore area ratio of the central region of the jth particle can be obtained, that is, aj , which reflects the pore distribution in the central area; identify and measure the pore area in the edge area, and divide the pore area in the edge area by the total area of the edge area to obtain the pore area ratio of the edge area of the jth particle, that is, bj , which reflects the pore distribution in the edge area. It can be understood that the pore area of the jth particle is equal to the sum of the pore areas of its central area and the edge area, and the total area of the jth particle is equal to the sum of the areas of its central area and the edge area.
[0056] In S23, for m particles j The average calculation is performed to obtain the pore area percentage of the core, that is, , which reflects the proportion of the pore area of the core in the entire negative electrode material.
[0057] S24, for each particle, by A j = aj / bj The ratio of the pore area percentage of the central area and the edge area of the jth particle is calculated, that is, the A of the jth particle. j This ratio can reflect the difference in pore structure characteristics between the inner and outer regions of the jth particle.
[0058] S25, A for m particles j The average calculation is performed to obtain the A value, which is the average of the ratio of the pore area percentage of the central area to the edge area. A reflects the average of the ratio of the pore area percentage of the inner area to the outer area in the entire negative electrode material, and is used to indicate the difference in property characteristics between the inner and outer areas of the particle.
[0059] The central region represents the average state of the inner region of the particle, and the edge region represents the average state of the outer region of the particle. In some embodiments, the central region is circular or elliptical, and the center of the central region is the center of the inner core section. The definition of the central region makes the analysis range cover the central part of the inner core section of the particle.
[0060] In some embodiments, the long axis of the central region is equal to 1 / 2 of the length of the transverse median line of the inner core section, and the short axis of the central region is equal to 1 / 2 of the length of the longitudinal median line of the inner core section. The inner core section has two transverse median lines and a longitudinal median line that are perpendicular to each other and pass through the center of the inner core section, and the long axis and short axis of the central region are 1 / 2 of the transverse median line and the longitudinal median line, respectively.
[0061] The D50 particle size is the particle size corresponding to when the volume cumulative distribution percentage in the sample reaches 50%, reflecting the average particle size of the negative electrode material. In some embodiments, the D50 particle size of the negative electrode material is 5 to 20 μm. By limiting the D50 particle size of the negative electrode material to an appropriate range, in addition to helping to further improve the initial coulombic efficiency of the secondary battery and reduce the expansion rate, it can also make the diffusion path of lithium ions shorter, which can reduce the transmission resistance of lithium ions during the embedding and de-embedding process, thereby improving the charging and discharging efficiency. In addition, it can also reduce the internal pores of the electrode and improve the energy density of the secondary battery.
[0062] Regular particle shapes help improve the cycle stability and life of secondary batteries. In some embodiments, the shape of the negative electrode material includes at least one of a sphere, an ellipsoid, and a quasi-spherical shape. The shape of the negative electrode material essentially refers to the particle shape of the negative electrode material. By defining the shape of the negative electrode material, it helps to form a more uniform electron and lithium ion transmission path, reduce local stress concentration, and improve the power density of the secondary battery.
[0063] Specific surface area (SSA) refers to the total surface area per unit mass of a material. In some embodiments, the specific surface area of the negative electrode material is 2 to 5 m 2 / g. By limiting the specific surface area of the negative electrode material within a moderate range, in addition to further improving the initial coulombic efficiency and reducing the expansion rate, a moderate diffusion path can be provided, which not only avoids the performance degradation caused by the electrolyte penetrating into the internal pores of the material, but also facilitates the rapid and uniform diffusion of lithium ions during the charge and discharge process, thereby improving the rate performance and cycle stability of the secondary battery. In addition, the contact between the electrolyte and the surface of the graphite material can be reduced, reducing the possibility of side reactions, such as electrolyte decomposition and co-embedding of solvent molecules.
[0064] Tap density (Tap) refers to the compactness of a material under physical vibration. In some embodiments, the tap density of the negative electrode material is 0.9~1.4g / cm 3. By limiting the tap density of the negative electrode material within a moderate range, it helps to improve the compaction density of the material during the electrode manufacturing process, reduce the internal pores of the electrode, improve the utilization rate of the negative electrode material and the energy density of the secondary battery, and at the same time reduce the contact area between the electrolyte and the graphite particles, thereby reducing the formation of the SEI film, reducing the irreversible capacity during the first charge and discharge, and further improving the first coulomb efficiency; it also helps to reduce the volume expansion during the cycle, reduce the mechanical stress between the particles, and prevent the formation of cracks. In addition, it helps to maintain the integrity of the electrode structure, prevent the active material from falling off the current collector, and help improve the cycle performance.
[0065] In some embodiments, the average pore size of the negative electrode material is 10 to 20 nm. By limiting the average pore size of the negative electrode material within the above range, firstly, it helps lithium ions to be more evenly embedded in the graphite layer during the first charge and discharge process, thereby facilitating the formation of a stable and dense SEI film, which can further improve the first coulomb efficiency. Secondly, limiting the average pore size can reduce the volume change of the material during the lithium ion embedding and de-embedding process, further reduce the expansion rate of graphite particles during the charge and discharge process, help improve the stability of the material structure, reduce the stress accumulation inside the secondary battery, and extend the service life of the secondary battery. In addition, lithium ions can diffuse relatively easily and quickly between graphite layers, which helps to increase the charge and discharge rate and shorten the charge and discharge time.
[0066] In some embodiments, the average particle size of the core is 5-20 μm, and the thickness of the coating layer is 2-100 nm, which can be adjusted according to actual needs.
[0067] In some embodiments, the mass ratio of the core to the coating layer is 100:(4-10), for example, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10 or a range consisting of any two of them; the mass ratio of the first amorphous carbon to the second amorphous carbon is (5-10):3, for example, 5:3, 6:3, 7:3, 8:3, 9:3, 10:3 or a range consisting of any two of them.
[0068] The negative electrode material of the present invention can be used as a negative electrode material in a secondary battery, and can effectively improve the first coulombic efficiency of the secondary battery and reduce the expansion rate. For example, in some embodiments, the first coulombic efficiency of the negative electrode material is ≥93.5%, and the first coulombic efficiency can be further achieved. ≥94%, the expansion rate of the pole piece after 20 cycles is ≤27.3%, and the expansion rate of the pole piece after 20 cycles can be further achieved. ≤25.9%, and the capacity is ≥362mAh / g.
[0069] The present invention does not limit the specific preparation process of the negative electrode material, as long as the above parameters are met. In some embodiments, the preparation method of the negative electrode material includes the following steps:
[0070] S1, performing a first mixing coating and a first heat treatment on the graphite raw material and the first part of the asphalt in sequence to obtain a composite;
[0071] S2, subjecting the composite to isostatic pressing and densification treatment, and then crushing the composite to obtain a first intermediate product;
[0072] S3, performing a second mixed coating on the first intermediate product and the second portion of asphalt to obtain a secondary coated product;
[0073] S4, performing a press process on the secondary coated product to obtain a second intermediate product;
[0074] S5, subjecting the second intermediate product to a second heat treatment to obtain a negative electrode material.
[0075] In S1, the graphite raw material is mixed and coated with the first part of asphalt. It can be understood that the graphite raw material and the asphalt are mixed under the temperature condition of the asphalt softening point. In the first mixed coating process, the first part of the asphalt is molten and mixed evenly with the graphite raw material to obtain a primary coating; the primary coating is subjected to a first heat treatment so that the molten first part of the asphalt is filled into the pores inside the graphite to obtain a composite. The mixed coating and the first heat treatment help to improve the density of the material. The graphite raw material can be spherical graphite with a D50 particle size of 1~20μm.
[0076] The specific mixing ratio of the graphite raw material and the first part of asphalt can be adjusted according to the material properties and requirements. The first part of asphalt is selected from at least one of petroleum asphalt, coal asphalt, and intermediate phase asphalt, and the D50 particle size of the asphalt is 2-3mm; the softening point of the first part of asphalt is 100~300℃. It can be understood that the temperature of the mixed coating is 100~300℃, and the mixed coating time is 10~60min; the first heat treatment can be carried out in a first inert atmosphere at 100~200℃ higher than the softening point of asphalt; the first inert atmosphere is to prevent oxidation of the material during the heat treatment process, and any inert gas can achieve this purpose, for example, it can include at least one of nitrogen, helium, and argon; the temperature of the first heat treatment is 200~600℃, and the time is 3~4h.
[0077] In S2, the composite is subjected to isostatic pressing and densification treatment to obtain an isostatic pressing product, and then the isostatic pressing product is crushed to obtain a first intermediate product. Further internal filling is achieved through isostatic pressing and densification treatment, which can effectively reduce the internal pores of the graphite, increase the density of the material, enhance its structural density, and improve the pore filling effect.
[0078] The specific pressure and time of isostatic pressing can be optimized according to the performance requirements of the material and the equipment capacity. For example, in some embodiments, during isostatic pressing, the filling effect of asphalt inside the graphite can be regulated by adjusting the pressure. For example, the isostatic pressing can be cold isostatic pressing or warm isostatic pressing, and the pressure of the isostatic pressing is 60-120 MPa, and the holding time is 1-60 min.
[0079] In S3, the first intermediate product and the second part of asphalt are subjected to a second mixing and coating. It can be understood that the first intermediate product and the second part of asphalt are mixed under the temperature condition of the softening point of asphalt. During the second mixing and coating process, the second part of asphalt is in a molten state and is evenly mixed with the first intermediate product, so that the second part of asphalt in a molten state is coated on the surface of the first intermediate product to obtain a secondary coating.
[0080] In some embodiments, the mass ratio of the graphite raw material to the asphalt is 100:(8-12), such as 100:8, 100:9, 100:10, 100:11, 100:12 or a range consisting of any two thereof. The mass of the asphalt refers to the sum of the masses of the first part of the asphalt and the second part of the asphalt, and the mass ratio of the first part of the asphalt to the second part of the asphalt is (5-10):3, such as 5:3, 6:3, 7:3, 8:3, 9:3, 10:3 or a range consisting of any two thereof.
[0081] In S4, a hydraulic press can be used to press the secondary coating to obtain a second intermediate product. The specific pressure, time, and number of cycles of the press process can be adjusted according to the actual equipment capacity and material requirements. For example, in some embodiments, the press conditions are: the pressure of the hydraulic press is 10~40MPa, the holding time is 0~2min, and the pressure is released for 0.5min and then slowly reciprocated 2~4 times. The short holding time can ensure that the material quickly forms a dense structure under high pressure, while avoiding equipment wear and reduced production efficiency caused by long-term pressure holding. It is suitable for continuous production processes and can improve production efficiency and equipment utilization.
[0082] In S5, the second intermediate product is subjected to a second heat treatment under a second inert atmosphere to ensure the graphitization degree of the material. After the second heat treatment, the negative electrode material is obtained after being dispersed, demagnetized and screened. The first part of the asphalt filled into the internal pores of the graphite is converted into the first amorphous carbon by the second heat treatment, and the second part of the asphalt coated on the surface is converted into the second amorphous carbon, thereby obtaining the negative electrode material having the above-mentioned special structure. The second heat treatment ensures that the material is stably carbonized at high temperature and improves its graphitization degree. Appropriate heat treatment temperature and time can affect the crystallinity and microstructure of graphite, so that the I D / I G Meet the above requirements.
[0083] The specific temperature and time of the second heat treatment can be adjusted according to the conditions of the heat treatment device and the performance target of the material. For example, in some embodiments, the temperature of the second heat treatment is greater than the temperature of the first heat treatment, for example, the temperature of the second heat treatment is 900~1500℃, and the time is 1~24h. Among them, the second inert atmosphere is to prevent oxidation of the material during the heat treatment process, and any inert gas can achieve this purpose, for example, it can include at least one of nitrogen, helium, and argon.
[0084] A second aspect of the present invention provides a negative electrode sheet, which includes the negative electrode material provided by the first aspect.
[0085] The negative electrode sheet of the present invention comprises a negative electrode current collector and a negative electrode material active layer disposed on at least one surface of the negative electrode current collector. The negative electrode material active layer comprises the negative electrode material provided in the first aspect. The negative electrode current collector may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, and may also be a composite current collector disclosed in any prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate. Since the negative electrode sheet comprises a negative electrode material with excellent performance, the negative electrode sheet is applied to a secondary battery, which helps to improve the first coulomb efficiency of the secondary battery and reduce the expansion rate.
[0086] The negative electrode material active layer also includes a binder to bind the negative electrode active material particles to facilitate the formation of a film layer, and can also improve the binding force between the negative electrode material active layer and the negative electrode current collector. In some embodiments, the binder may include but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic (ester) styrene butadiene rubber, epoxy resin or nylon, etc.
[0087] The negative electrode material active layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.
[0088] When preparing the negative electrode sheet, the negative electrode material, the conductive agent and the binder can be dispersed in an appropriate amount of solvent, and the mixture is stirred and mixed to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector, and the negative electrode sheet is obtained after drying, rolling and cutting. In a specific embodiment, the negative electrode active layer includes 70% to 99% of the negative electrode material, 0.5% to 15% of the conductive agent, and 0.5% to 15% of the binder in terms of mass percentage.
[0089] Among them, the conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene; the binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyvinyl alcohol, and sodium polyacrylate.
[0090] A third aspect of the present invention provides a secondary battery, the secondary battery comprising the negative electrode sheet provided by the second aspect.
[0091] Due to the inclusion of the above-mentioned negative electrode sheet with excellent performance, the secondary battery has excellent first coulombic efficiency and low expansion rate.
[0092] Specifically, the secondary battery includes a housing, an electrode assembly and an electrolyte. The electrode assembly and the electrolyte are both located in the housing.
[0093] The outer shell may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), for example, a soft-pack battery. In other embodiments, it may also be a steel shell battery, an aluminum shell battery, etc.
[0094] See also Figure 3 and Figure 4 The electrode assembly 100 includes a positive electrode sheet 101, a negative electrode sheet 102 and a separator 103, wherein the separator 103 is disposed between the positive electrode sheet 101 and the negative electrode sheet 102. Figure 3 , active ions (such as lithium ions) are deintercalated from the lattice of the positive electrode material (such as the lithiated intercalation compound) of the positive electrode sheet 101, pass through the separator 103 through the electrolyte, reach the negative electrode sheet 102 and insert into the lattice of the negative electrode material. Figure 4 , active ions (such as lithium ions) are deintercalated from the lattice of the negative electrode material of the negative electrode sheet 102, pass through the isolation membrane 103 through the electrolyte, reach the positive electrode sheet 101 and are embedded in the lattice of the positive electrode material (such as the lithiated intercalation compound), generating electrons that travel from the negative electrode sheet 102 through the external circuit to the positive electrode sheet 101, and the reverse movement of the electrons forms an electric current that can be used by electrical appliances.
[0095] In some embodiments, the electrode assembly 100 may be a laminated structure, which is formed by alternately stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102. In other embodiments, the electrode assembly 100 may also be a wound structure, which is formed by stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102 in sequence and then winding them.
[0096] The positive electrode sheet 101 includes a positive electrode current collector and a positive electrode material active layer provided on at least one surface of the positive electrode current collector. The positive electrode current collector may be made of aluminum foil or nickel foil, or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and a polymer substrate. The positive electrode material active layer includes a positive electrode active material, and the positive electrode active material includes a compound that reversibly embeds and deintercalates lithium ions (i.e., a lithiated intercalation compound). In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese and nickel. In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4) or at least one of lithium iron phosphate (LiFePO4).
[0097] The positive electrode material active layer also includes a binder to bond the positive electrode active material particles to facilitate the formation of a film layer, and at the same time, it can also improve the bonding force between the positive electrode material active layer and the positive electrode current collector. In some embodiments, the binder may include but is not limited to at least one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon.
[0098] The positive electrode material active layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.
[0099] The isolation membrane 103 includes a membrane layer with a porous structure, and its material includes but is not limited to at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, the isolation membrane 103 can be a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite membrane.
[0100] The electrolyte has the function of conducting ions between the positive electrode sheet 101 and the negative electrode sheet 102. The state of the electrolyte can be one or more of a gel state, a solid state and a liquid state. In some embodiments, the electrolyte is an electrolyte. The electrolyte plays the role of conducting active ions between the positive electrode sheet 101 and the negative electrode sheet 102. In some embodiments, the electrolyte includes a lithium salt and an organic solvent. The lithium salt may be selected from, but not limited to, one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium tetraphenylborate (LiB(C6H5)4), lithium methanesulfonate (LiCH3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(SO2CF3)2), tris(trifluoromethylsulfonyl)methyl lithium (LiC(SO2CF3)3), lithium bis(oxalatoborate) (LiBOB) and lithium difluorophosphate (LiPO2F2). For example, the lithium salt is selected from LiPF6 because it can provide high ionic conductivity and improve cycle characteristics. The organic solvent may be a carbonate compound, a carboxylate compound, an ether compound, a nitrile compound, other organic solvents or a combination thereof. Examples of carbonate compounds include, but are not limited to, diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), ethylmethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylethylene carbonate (VEC), fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, or combinations thereof.
[0101] When preparing secondary batteries, the positive electrode sheets, separators and negative electrode sheets are wound or stacked to obtain battery cells, which are then packaged in pre-stamped aluminum-plastic films. After the packaged batteries are dried to remove moisture, the electrolyte is injected into the dry batteries. After the batteries are placed, formed and sealed for a second time, the preparation of the secondary batteries is completed.
[0102] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0103] Example 1
[0104] The method for preparing the negative electrode material of this embodiment comprises the following steps:
[0105] S1, 20 kg of graphite raw material (D50 particle size is 16 μm) and 1.6 kg of asphalt (softening point 250°C) are added into a VC mixer and mixed for 25 min. After uniform mixing, low-temperature heat treatment is performed at 400°C for 4 h under a nitrogen atmosphere. After cooling to room temperature, a composite is obtained;
[0106] S2, subjecting the composite to isostatic pressing and densification treatment, with a maximum isostatic pressing pressure of 60 MPa, maintaining the pressure for 15 minutes, and then crushing the material to about 16 μm to obtain a first intermediate product;
[0107] S3, adding the first intermediate product and 0.6 kg of asphalt (softening point 250°C) into a VC mixer and mixing for 25 minutes to obtain a secondary coating;
[0108] S4, pressing the secondary coated product in a hydraulic press at a pressure of 30 MPa, maintaining the pressure for 0.5 min, and reciprocating for 3 times to obtain a second intermediate product;
[0109] S5, subjecting the second intermediate product to high-temperature heat treatment, carbonizing it at 1250° C. for 16 h in a nitrogen protective atmosphere, and breaking it up, demagnetizing it, and sieving it after carbonization to obtain the negative electrode material of this embodiment.
[0110] Example 2
[0111] The method for preparing the negative electrode material of this embodiment comprises the following steps:
[0112] S1, 20 kg of graphite raw material (D50 particle size is 16 μm) and 1.6 kg of asphalt (softening point 180°C) are added into a VC mixer and mixed for 25 min. After uniform mixing, low-temperature heat treatment is performed at 350°C for 4 h under a nitrogen atmosphere. After cooling to room temperature, a composite is obtained;
[0113] S2, subjecting the composite to isostatic pressing and densification treatment, with a maximum isostatic pressing pressure of 50 MPa, maintaining the pressure for 15 minutes, and then crushing the material to about 16 μm to obtain a first intermediate product;
[0114] S3, adding the first intermediate product and 0.6 kg of asphalt (softening point 180°C) into a VC mixer and mixing for 30 minutes to obtain a secondary coating;
[0115] S4, pressing the secondary coated product in a hydraulic press at a pressure of 30 MPa, maintaining the pressure for 0.5 min, and reciprocating for 3 times to obtain a second intermediate product;
[0116] S5, subjecting the second intermediate product to high-temperature heat treatment, carbonizing it at 1150° C. for 12 h in a nitrogen protective atmosphere, and breaking it up, demagnetizing it, and sieving it after carbonization to obtain the negative electrode material of this embodiment.
[0117] Example 3
[0118] The method for preparing the negative electrode material of this embodiment comprises the following steps:
[0119] S1, 20 kg of graphite raw material (D50 particle size is 16 μm) and 1.0 kg of asphalt (softening point 180°C) are added into a VC mixer and mixed for 25 min. After uniform mixing, low-temperature heat treatment is performed at 350°C for 4 h under a nitrogen atmosphere. After cooling to room temperature, a composite is obtained;
[0120] S2, subjecting the composite to isostatic pressing and densification treatment, with a maximum isostatic pressing pressure of 50 MPa, maintaining the pressure for 15 minutes, and then crushing the material to about 16 μm to obtain a first intermediate product;
[0121] S3, adding the first intermediate product and 0.6 kg of asphalt (softening point 180° C.) into a VC mixer and mixing for 25 minutes to obtain a first intermediate product;
[0122] S4, pressing the first intermediate product in a hydraulic press at a pressure of 25 MPa, maintaining the pressure for 0.5 min, and repeating for 3 times to obtain a second intermediate product;
[0123] S5, subjecting the second intermediate product to high-temperature heat treatment and carbonizing it at 1150° C. for 10 h under a nitrogen atmosphere, and breaking it up, demagnetizing it, and sieving it after carbonization to obtain the negative electrode material of this embodiment.
[0124] Example 4
[0125] The method for preparing the negative electrode material of this embodiment comprises the following steps:
[0126] S1, 20 kg of graphite raw material (D50 particle size is 14.5 μm) and 1.6 kg of asphalt (softening point 250 ° C) are added to a VC mixer and mixed for 25 min. After uniform mixing, they are subjected to low-temperature heat treatment at 400 ° C for 4 h under a nitrogen atmosphere. After cooling to room temperature, a composite is obtained;
[0127] S2, subjecting the composite to isostatic pressing and densification treatment, with a maximum isostatic pressing pressure of 70 MPa, maintaining the pressure for 15 minutes, and then crushing the material to about 14.5 μm to obtain a first intermediate product;
[0128] S3, adding the first intermediate product and 0.6 kg of asphalt (softening point 250°C) into a VC mixer and mixing for 30 minutes to obtain a secondary coating;
[0129] S4, pressing the secondary coated product in a hydraulic press at a pressure of 30 MPa, maintaining the pressure for 0.5 min, and reciprocating for 3 times to obtain a second intermediate product after rough crushing;
[0130] S5, subjecting the second intermediate product to high-temperature heat treatment and carbonizing it at 1250° C. for 16 h under a nitrogen protective atmosphere, and breaking it up, demagnetizing it, and sieving it after carbonization to obtain the negative electrode material of this embodiment.
[0131] Example 5
[0132] The method for preparing the negative electrode material of this embodiment comprises the following steps:
[0133] S1, 20 kg of graphite raw material (D50 particle size is 12 μm) and 1.6 kg of asphalt (softening point 250°C) are added into a VC mixer and mixed for 25 min. After uniform mixing, low-temperature heat treatment is performed at 400°C for 4 h under a nitrogen atmosphere. After cooling to room temperature, a composite is obtained;
[0134] S2, subjecting the composite to isostatic pressing and densification treatment, with a maximum isostatic pressing pressure of 60 MPa, maintaining the pressure for 15 minutes, and then crushing the material to about 12 μm to obtain a first intermediate product;
[0135] S3, adding the first intermediate product and 0.6 kg of asphalt (softening point 250°C) into a VC mixer and mixing for 30 minutes to obtain a secondary coating;
[0136] S4, pressing the secondary coated product in a hydraulic press at a pressure of 30 MPa, maintaining the pressure for 0.5 min, and reciprocating for 3 times, and obtaining a second intermediate product after rough crushing;
[0137] S5, subjecting the second intermediate product to high-temperature heat treatment, carbonizing it at 1250° C. for 14 h in a nitrogen protective atmosphere, and breaking it up, demagnetizing it, and sieving it after carbonization to obtain the negative electrode material of this embodiment.
[0138] Example 6
[0139] The method for preparing the negative electrode material of this embodiment comprises the following steps:
[0140] S1, 20 kg of graphite raw material (D50 particle size is 10 μm) and 1.6 kg of asphalt (softening point 250°C) are added into a VC mixer and mixed for 25 min. After uniform mixing, low-temperature heat treatment is performed at 400°C for 4 h under a nitrogen atmosphere. After cooling to room temperature, a composite is obtained;
[0141] S2, subjecting the composite to isostatic pressing and densification treatment, with a maximum isostatic pressing pressure of 60 MPa, maintaining the pressure for 15 minutes, and then crushing the material to about 10 μm to obtain a first intermediate product;
[0142] S3, adding the first intermediate product and 0.6 kg of asphalt (softening point 250°C) into a VC mixer and mixing for 25 minutes to obtain a secondary coating;
[0143] S4, pressing the secondary coated product in a hydraulic press at a pressure of 30 MPa, maintaining the pressure for 0.5 min, and reciprocating for 3 times, and obtaining a second intermediate product after rough crushing;
[0144] S5, subjecting the second intermediate product to high-temperature heat treatment, carbonizing it at 1250° C. for 18 h in a nitrogen protective atmosphere, and breaking it up, demagnetizing it, and sieving it after carbonization to obtain the negative electrode material of this embodiment.
[0145] Example 7
[0146] The method for preparing the negative electrode material of this embodiment comprises the following steps:
[0147] S1, 20 kg of graphite raw material (D50 particle size is 16 μm) and 0.7 kg of asphalt (softening point 180°C) are added into a VC mixer and mixed for 25 min. After uniform mixing, low-temperature heat treatment is performed at 350°C for 4 h under a nitrogen atmosphere. After cooling to room temperature, a composite is obtained;
[0148] S2, subjecting the composite to isostatic pressing and densification treatment, with a maximum isostatic pressing pressure of 50 MPa, maintaining the pressure for 15 minutes, and then crushing the material to about 16 μm to obtain a first intermediate product;
[0149] S3, adding the first intermediate product and 0.3 kg of asphalt (softening point 180° C.) into a VC mixer and mixing for 25 minutes to obtain a first intermediate product;
[0150] S4, pressing the first intermediate product in a hydraulic press at a pressure of 25 MPa, maintaining the pressure for 0.5 min, and repeating for 3 times to obtain a second intermediate product;
[0151] S5, subjecting the second intermediate product to high-temperature heat treatment and carbonizing it at 1150° C. for 12 h under a nitrogen protective atmosphere, and breaking it up, demagnetizing it, and sieving it after carbonization to obtain the negative electrode material of this embodiment.
[0152] Example 8
[0153] The method for preparing the negative electrode material of this embodiment comprises the following steps:
[0154] S1, 20 kg of graphite raw material (D50 particle size is 16 μm) and 2.0 kg of asphalt (softening point 180°C) are added into a VC mixer and mixed for 25 min. After uniform mixing, low-temperature heat treatment is performed at 350°C for 4 h under a nitrogen atmosphere. After cooling to room temperature, a composite is obtained;
[0155] S2, subjecting the composite to isostatic pressing and densification treatment, with a maximum isostatic pressing pressure of 50 MPa, maintaining the pressure for 15 minutes, and then crushing the material to about 16 μm to obtain a first intermediate product;
[0156] S3, adding the first intermediate product and 1.0 kg of asphalt (softening point 180° C.) into a VC mixer and mixing for 25 minutes to obtain a first intermediate product;
[0157] S4, pressing the first intermediate product in a hydraulic press at a pressure of 25 MPa, maintaining the pressure for 0.5 min, and repeating for 3 times to obtain a second intermediate product;
[0158] S5, subjecting the second intermediate product to high-temperature heat treatment and carbonizing it at 1250° C. for 18 h under a nitrogen protective atmosphere, and breaking it up, demagnetizing it and screening it after carbonization to obtain the negative electrode material of this embodiment.
[0159] Example 9
[0160] S1, 20 kg of graphite raw material (D50 particle size is 16 μm) and 2.5 kg of asphalt (softening point 180°C) are added into a VC mixer and mixed for 25 min. After uniform mixing, low-temperature heat treatment is performed at 350°C for 4 h under a nitrogen atmosphere. After cooling to room temperature, a composite is obtained;
[0161] S2, subjecting the composite to isostatic pressing and densification treatment, with a maximum isostatic pressing pressure of 50 MPa, maintaining the pressure for 15 minutes, and then crushing the material to about 16 μm to obtain a first intermediate product;
[0162] S3, adding the first intermediate product and 1.5 kg of asphalt (softening point 180° C.) into a VC mixer and mixing for 25 minutes to obtain a first intermediate product;
[0163] S4, pressing the first intermediate product in a hydraulic press at a pressure of 25 MPa, maintaining the pressure for 0.5 min, and repeating for 3 times to obtain a second intermediate product;
[0164] S5, subjecting the second intermediate product to high-temperature heat treatment and carbonizing it at 1250° C. for 18 h under a nitrogen protective atmosphere, and breaking it up, demagnetizing it and screening it after carbonization to obtain the negative electrode material of this embodiment.
[0165] Comparative Example 1
[0166] The preparation method of the negative electrode material of this comparative example comprises the following steps:
[0167] 20 kg of graphite raw material (D50 particle size is 16 μm) and 2.2 kg of asphalt (softening point 250°C) were added to a VC mixer and mixed for 25 minutes. After mixing, the materials were carbonized at 1250°C for 16 hours under a nitrogen atmosphere. After carbonization, the negative electrode material of this comparative example was obtained by breaking up, demagnetizing and sieving.
[0168] Comparative Example 2
[0169] The preparation method of the negative electrode material of this comparative example comprises the following steps:
[0170] 20 kg of graphite raw material (D50 particle size is 16 μm), 2.25 kg of asphalt (softening point 250°C) and 40 g of graphene powder were mixed in a VC mixer for 25 min, and then heat treated at 400°C to make the asphalt and graphene powder evenly and tightly adhere to the surface of graphite particles. After the mixture is carbonized at 1250°C for 16 h under a nitrogen protective atmosphere, the negative electrode material of this comparative example is obtained after being dispersed, demagnetized and sieved.
[0171] Comparative Example 3
[0172] The preparation method of the negative electrode material of this comparative example comprises the following steps:
[0173] S1, 20kg of graphite raw material (D50 particle size is 16μm) is subjected to isostatic pressing and densification treatment, the maximum isostatic pressing pressure is 60MPa, and the pressure is maintained for 15min; the material is crushed and pressed in a hydraulic press, the hydraulic press pressure is 30MPa, and the pressure is maintained for 0.5min. After reciprocating 3 times, it is crushed to about 16μm to obtain a densified product;
[0174] S2, the densified product and 2.2 kg of asphalt (softening point 250°C) were added into a VC mixer and mixed for 25 minutes, and then carbonized at 1250°C for 16 hours under a nitrogen atmosphere. After carbonization, the negative electrode material of this comparative example was obtained by breaking up, demagnetizing and sieving.
[0175] Test example
[0176] 1. Cross-section morphology test
[0177] The negative electrode material was milled into particle samples using an ion milling machine (HITACHI E3500) to observe the cross-section of the particles, and the samples were placed under a high-power electron microscope (HITACHI S4800) to observe the cross-section of the particles. The magnification of a single particle was 2.5kX~9.0kX to ensure that the cross-section showed a complete single particle.
[0178] Select at least 20 particles and cut through the center of each particle to expose the cross section. Take the intersection of the horizontal median line and the vertical median line of the core cross section of a single particle as the center of the ellipse. The major axis of the ellipse is 1 / 2 of the length of the horizontal median line, and the minor axis is 1 / 2 of the length of the vertical median line. Use the ellipse to divide the core cross section into a central area (a1) and an edge area (b1), as shown in Figure 2. Figure 2 shown.
[0179] The pore area ratio of the core section of a single particle was counted and calculated using the Aztec Feature software of OXFORD Instruments SEM electron microscope. , the pore area ratio in the central area , the pore area ratio of the edge area And the ratio of the pore area in the central area to the pore area in the edge area (A j ),in, = pore area in the center of the jth particle section / area of the center*100%, = pore area of the edge region of the jth particle section / edge region area*100%, = pore area of the core section of the jth particle / area of the core section*100%, A j = / ;
[0180] The pore area percentage of the entire negative electrode material core section is calculated according to the following formula ( ) and the average value of the ratio of the pore area to the cross-sectional area in the central area and the edge area (A):
[0181]
[0182]
[0183] Wherein, m≥20, 1≤j≤m, and j and m are positive integers.
[0184] 2.I D / I G test
[0185] The Raman scattering spectrum of the negative electrode material was tested using an InVia confocal Raman spectrometer with a laser wavelength of 532 nm. The peak of material D is at 1350 cm -1 The G peak is located at 1580 cm -1 Nearby, I D / I G The value is the D / G peak intensity ratio. The Raman Mapping area diagram of a single particle cross section is shown in Figure 1 shown.
[0186] Select at least 15 particles, cut through the center of each particle to expose the cross section; select a rectangular area with a width of 1~6μm and a length equal to the short diameter of the cross section of the inner core of each particle, perform Raman mapping on the rectangular area, and divide the mapping area into an inner rectangular area a and an outer rectangular area b. Determine the characteristic peak of the material by peak fitting the Raman scattering spectrum of each point. The D peak is located at 1350cm -1 The G peak is located at 1580 cm -1 The intensity ratio of the D peak to the G peak in the inner rectangular area a and the outer rectangular area b of each particle is calculated (I D / I G ) value, K ai is the I of the rectangular area in the i-th particle D / I G , K bi I is the outer rectangular area of the i-th particle D / I G ;
[0187] The I of the inner region is calculated according to the following formula D / I G The mean value (K a ), the inner area and the outer area I D / I G The mean of the ratio (K):
[0188]
[0189] K i =K ai / K bi
[0190]
[0191] Wherein, n≥15, 1≤i≤n, and i and n are positive integers.
[0192] 3. Specific surface area SSA test
[0193] The JW-DX dynamic specific surface area measuring instrument is used to test the specific surface area of the negative electrode material. Based on the relevant theories of physical adsorption, the continuous flow method proposed by Nelsen and Eggertsen is used as the structure to determine the specific surface area of the solid. A mixed gas with hydrogen as the carrier and nitrogen as the adsorption gas is passed into the sample tube. When the sample tube is immersed in liquid nitrogen to reach a low temperature environment, the nitrogen in the mixed gas will be physically adsorbed by the sample until the adsorption is saturated. At this time, the proportion of nitrogen in the mixed gas will change. During the adsorption process, the high-precision thermal conductivity detection instrument will complete the detection and calculation work.
[0194] 4. D50 particle size test
[0195] The D50 particle size of the negative electrode material was tested using the Malvern 3000 laser particle size analyzer. The sample, a small amount of dispersant (a mixture of ethanol, pure water and low-foaming surfactant) and pure water were added to a 50 mL beaker. The sample was fully stirred with a glass rod to disperse the sample evenly. The sample was transferred to the sample cell of the Malvern 3000 laser particle size analyzer, and the pump speed of the equipment was set to 2400~2500r / min and the frequency was 19.5 Hz for particle size testing.
[0196] 5. Tap density test
[0197] The tap density of the negative electrode material was tested using the Quantachrome Dual Autotap device. 100 mL of the negative electrode material sample was placed in a measuring cylinder and mechanically vibrated 1000 times. The sample mass and volume after tapping were obtained, and the tap density was calculated according to the formula: tap density (g / cm³) = sample mass / volume after tapping.
[0198] 6. Average pore diameter d test
[0199] The average pore size d of the negative electrode material was tested using BSD-660M A6M. The static capacity method was used, degassing was performed at 300°C for 300 minutes, nitrogen (77.3K) was used as the adsorbate, and then the amount of nitrogen adsorbed at different pressures was measured. By analyzing the adsorption isotherm, the average pore size d of the negative electrode material can be determined.
[0200] 7. Electrochemical performance test
[0201] The negative electrode materials of the embodiment and the comparative example, carboxymethyl cellulose and styrene-butadiene rubber were dissolved in pure water at a mass ratio of 96.5:1.5:2, and the solid content was controlled to be 50% to obtain a negative electrode slurry; the negative electrode slurry was coated on a copper foil current collector, and after vacuum drying at 95° C., roller pressing and pressurizing, a negative electrode sheet was obtained; a metal lithium sheet was used as a counter electrode, and a button battery was assembled in a glove box filled with argon.
[0202] The button cell was charged and discharged at a current density of 0.1C in the charge and discharge range of 0.01~1.5V to obtain the first reversible specific capacity, first cycle charging capacity and first cycle discharge capacity. The first coulombic efficiency (first efficiency) was calculated according to the first coulombic efficiency = first cycle discharge capacity / first cycle charging capacity.
[0203] The electrode expansion rate test was conducted using the battery electrode thickness change measurement device and system disclosed in patent document CN209991940U. The negative electrode material, carboxymethyl cellulose, and styrene-butadiene rubber were uniformly mixed in a mass percentage of 96.5:1.5:2, and the solid content was controlled at 50% to obtain a negative electrode slurry; the negative electrode slurry was coated on the copper foil current collector, and after vacuum drying and roller pressing, a compaction density of 1.60g / cm 3 The negative electrode sheet was tested for its initial thickness d1; the positive electrode active material lithium cobalt oxide, conductive carbon black, and polyvinylidene fluoride were mixed evenly in a mass ratio of 96.5:2:1.5 and then coated on an aluminum foil (single side) to obtain a positive electrode sheet. The positive and negative electrode sheets prepared above were loaded into a self-made three-electrode test device for testing, which can record the thickness change of the electrode sheet in situ.
[0204] The test was conducted according to the following charge and discharge system: in the first week, the battery was charged at a constant rate of 0.01C for 30 minutes, then at a constant rate of 0.05C for 30 minutes, then at a constant rate of 0.1C to 4.2V, and then the voltage reached the upper limit of 4.2V. The current gradually decreased to 0.01C to end the charging, and then discharged to 3V at 0.1C; in the second week, the battery was charged at a constant rate of 0.2C to 4.2V; after the voltage reached 4.2V, the current gradually decreased to 0.01C. At the end of the cycle, discharge at a constant rate of 0.2C to 3V; charge at a constant rate of 0.5C to 4.2V from the 3rd to the 20th week, charge at a constant voltage after the voltage reaches 4.2V, and reduce the current to 0.01C to end the charge, and then discharge at a constant rate of 0.5C to 3V; charge at a constant rate of 0.5C to 4.2V in the last half cycle, charge at a constant voltage after the voltage reaches 4.2V, and reduce the current to 0.01C to end, disassemble the battery, and test the thickness d2 of the negative electrode after 20 cycles. Calculate the expansion rate according to the expansion rate of the electrode = (d2-d1) / d1×100%.
[0205] Table 1
[0206]
[0207] In Table 1, d is the average pore size of the negative electrode material.
[0208] According to Table 1, in the negative electrode materials of Examples 1 to 9, the graphite is filled with amorphous carbon, and all satisfy 0.4≤K a ≤0.7, 0.5≤K<0.9, while Comparative Example 1 and Comparative Example 3 do not satisfy 0.5≤K≤0.9, 0.4≤K a ≤0.7, the negative electrode material of Comparative Example 2 only satisfies 0.5≤K≤0.9, but does not satisfy 0.4≤K a≤0.7, the negative electrode materials of Examples 1 to 9 have higher initial coulombic efficiency, lower expansion rate and higher capacity than those of Comparative Examples 1 to 3. a ≤0.7, 0.5≤K<0.9, can reduce Li + The structural expansion caused by entering and exiting the graphite layers improves the structural stability of the material, and for the first time, the coulombic efficiency, expansion performance and capacity are improved.
[0209] Furthermore, compared with Examples 7, 8, and 9, the negative electrode materials of Examples 1 to 6 satisfy 0.5≤K≤0.9, 0.4≤K a ≤0.7, while making the pore area percentage of the core Satisfaction: 2% ≤ ≤5%, and further making the average value A of the ratio of the pore area percentage of the inner layer region to the outer layer region satisfy 1.2≤A≤2.0, which can further improve the initial coulombic efficiency, expansion performance and capacity. The negative electrode material of Example 9 does not satisfy 2%≤ ≤5%, the improvement of the electrochemical performance of the negative electrode material is limited, and the performance is worse than that of Examples 1 to 6. The negative electrode materials of Example 7 do not meet 1.2≤A≤2.0, and the negative electrode materials of Example 8 do not meet 2%≤ ≤5%, the improvement of the electrochemical performance of the negative electrode material is limited, and the performance is worse than that of Examples 1 to 6. The negative electrode materials of Example 9 do not meet the requirement of 2%≤ ≤5%, 1.2≤A≤2.0, which is worse than that of Examples 7-8.
[0210] In Examples 1 to 6, by coating in batches and adopting low-temperature heat treatment, pressing treatment, high-temperature heat treatment and other steps, the particles are filled with amorphous carbon, the internal defects of the particles are improved, the pores in the inner layer and the outer layer are filled, especially the pores in the outer layer are filled, so that the material meets 0.5≤K≤0.9, 0.4≤K a ≤0.7,1.2≤A≤2.0,2%≤ ≤5%, the graphite negative electrode material has the advantages of high density and low expansion, and the graphite negative electrode material is applied to secondary lithium-ion batteries to show excellent electrochemical performance. In Comparative Example 1, the amorphous carbon failed to fill into the graphite, and neither 0.5≤K≤0.9 nor 0.4≤K a ≤0.7, and does not meet 1.2≤A≤2.0, 2%≤ ≤5%, resulting in poor initial coulombic efficiency, capacity and expansion performance of the negative electrode material; Comparative Example 2 introduces a small amount of graphene, although it satisfies 0.5≤K≤0.9, but does not satisfy 0.4≤K a ≤0.7 and 1.2≤A ≤2.0,2%≤ ≤5%, the first coulombic efficiency, capacity and expansion performance are improved compared with comparative example 1, but the improvement effect is limited. Comparative example 3 uses densification technology to reduce the internal pores of graphite before coating with asphalt, but amorphous carbon fails to be filled into the graphite to the maximum extent, so that the negative electrode material satisfies 1.2≤A≤2.0, 2%≤ ≤5%, but does not satisfy 0.5≤K≤0.9, 0.4≤K a ≤0.7, the first coulombic efficiency and expansion performance are improved compared with comparative examples 1 and 2, but the capacity is reduced compared with comparative example 2, and the degree of improvement is limited.
[0211] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A negative electrode material, characterized in that: The negative electrode material comprises a core and a coating layer, wherein the coating layer is located on the surface of the core, the core comprises natural graphite and a first amorphous carbon filled in the pores of the natural graphite, and the coating layer comprises a second amorphous carbon; The Raman spectrum of the negative electrode material has a D peak and a G peak, and the intensity ratio of the D peak to the G peak is 1 D / I G ; The inner core includes an inner layer region and an outer layer region located outside the inner layer region, and the outer layer region is adjacent to the cladding layer; The inner region I D / I G The mean value is K a , the inner region and the outer region I D / I G The mean of the ratio is K; Satisfy: 0.4≤K a ≤0.7, 0.5≤K<0.
9.
2. The negative electrode material according to claim 1, characterized in that The pore area percentage of the core is , meet: 2% ≤ ≤5%.
3. The negative electrode material according to claim 2, characterized in that The average value of the ratio of the pore area percentage of the inner layer region to the outer layer region is A, which satisfies: 1.2≤A≤2.
0.
4. The negative electrode material according to any one of claims 1 to 3, characterized in that The D50 particle size of the negative electrode material is 5 μm to 20 μm.
5. The negative electrode material according to any one of claims 1 to 3, characterized in that The shape of the negative electrode material includes at least one of a sphere, an ellipsoid, and a quasi-spherical shape.
6. The negative electrode material according to any one of claims 1 to 3, characterized in that The specific surface area of the negative electrode material is 2 to 5 m 2 / g.
7. The negative electrode material according to any one of claims 1 to 3, characterized in that The tap density of the negative electrode material is 0.9-1.4 g / cm 3 .
8. The negative electrode material according to any one of claims 1 to 3, characterized in that The average pore size of the negative electrode material is 10-20 nm.
9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises the negative electrode material according to any one of claims 1 to 8.
10. A secondary battery, characterized in that: The secondary battery comprises the negative electrode sheet according to claim 9.
Citation Information
Patent Citations
Negative electrode material, and electrochemical device and electronic apparatus comprising same
CN113066977A
Graphite negative electrode material, preparation method thereof and lithium ion battery
CN114497546A
Secondary battery and electric device
CN117558918A
Negative electrode material and preparation method thereof, negative electrode plate, battery and electric equipment
CN118693263A
Negative electrode active material, negative electrode and lithium ion secondary battery
JP6278135B1
Cited By
Negative electrode material, negative electrode sheet and secondary battery
WO2026098721A1
Graphite material and preparation method therefor, negative electrode sheet, battery and electric device
WO2026145779A1